Climate Change Adaptation in Coastal Cities A Guidebook for Citizens, Public Officials and Planners - Major, David (Helsinki University Press, 2021)
This guidebook presents a framework for climate adaptation planning for coastal cities, large and small, focused on the central roles of citizens, public officials, and planners. The book is designed to help all stakeholders in coastal cities understand and develop effective adaptation measures in a sustainable way. Within a framework of eight key planning steps, guidance is provided for stakeholders in the adaptation process from initial assessments of climate impacts to final planning. The work sets out general principles and methods of adaptation to climate change for many types of coastal communities. Adaptation is seen throughout the work as a process that should take into account all coastal assets, including economic, environmental, social, cultural and historical assets, with due attention to disadvantaged communities. Among the adaptation elements covered in the book are: a review of the current climate situation; climate impacts and vulnerabilities; climate models and future scenarios; physical, economic, social and other characteristics of coastal cities and towns; the range of available adaptations, including management, infrastructure, and policy adaptations; evaluation of projects and programs; and working together to develop and finance adaptations. Numerous tables are presented to help organize information and guide planning, and examples of adaptation challenges and opportunities are provided from both developed and developing coastal cities and towns. The volume is copiously illustrated, with extensive up-to-date references to provide the reader with additional sources of information.